1981
DOI: 10.1161/01.res.48.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Regional edema formation in isolated perfused dog lungs.

Abstract: SUMMARY Studies using gravimetric analysis of lungs of frozen animals have suggested that the differences in pulmonary microvascular pressure between non-dependent and dependent lung do not influence the formation of regional pulmonary edema. We wondered if the inability to detect variation in regional extravascular lung water (EVLW) was due to the slow freezing process and, therefore, reassessed the distribution of EVLW in vertically suspended isolated perfused dog lungs with a radioisotopic technique that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…Consequently, it did not accumulate preferentially in the dependent lung regions. This finding is in accordance with previous reports obtained in a number of animal experiments of respiratory failure using different measurement techniques [19][20][21] and in cardiogenic pulmonary oedema [22], where a nongravitational distribution of oedema has been described. The reasons why oedema does not distribute according to the gravity are substantially unknown; however, it appears that the primary mechanism leading to oedema, at least in ARDS, acts equally in each part of the lung and that oedema cannot move freely through the interstitial space.…”
Section: Lung-structure Function Relationships In Early Ards: Homogensupporting
confidence: 93%
“…Consequently, it did not accumulate preferentially in the dependent lung regions. This finding is in accordance with previous reports obtained in a number of animal experiments of respiratory failure using different measurement techniques [19][20][21] and in cardiogenic pulmonary oedema [22], where a nongravitational distribution of oedema has been described. The reasons why oedema does not distribute according to the gravity are substantially unknown; however, it appears that the primary mechanism leading to oedema, at least in ARDS, acts equally in each part of the lung and that oedema cannot move freely through the interstitial space.…”
Section: Lung-structure Function Relationships In Early Ards: Homogensupporting
confidence: 93%
“…The fractional blood flow related to the fractional weight of the longitudinal slices increases from apex to bases, reflecting either the capillary density or diameter per unit of tissue. The nongravitational distribution of edema, as observed in this study, has been found both in patients (21) and in animal models (22,23). Therefore, it is possible that at first the edema increases according to the flow distribution.…”
Section: Oleic Acid-injured Lungsupporting
confidence: 73%
“…The loss of vasoconstrictor ability was not unique to hypoxia, however, as the postendotoxin lung vessels also failed to constrict to A II and PGF2, infusions (Table I). Mean wet-to-bloodless dry weight ratios in three of these lungs was 3.11, which is normal in our laboratory (28), suggesting the pulmonary vascular hyporesponsivity In association with this hyporesponsivity there was a rise in prostacyclin from nondetectable levels in seven of eight dogs before endotoxin and at 5 min after endotoxin to a mean of 360 pg/ml (± 130 SEM) (P < 0.01) with prostacyclin now detectable in all eight dogs (Fig. 2).…”
Section: Resultssupporting
confidence: 56%